Marvin Redpost : alone in his teacher's house - Sachar, Louis, 1954-; Sullivan, Barbara, 1957- (New York : Random House, 1994)
Marvin is pleased when his teacher asks him to take care of her dog while she's away, but he soon finds that there's more pressure involved than he likes.
Teacher's pet -- The key -- Mature and responsible -- The substitute -- Nothing in--nothing out -- Some dog food is eaten -- Liver -- Where's Waldo? -- Do something! -- Ma -- Waiting -- I'm sorry.
"A Stepping Stone book."
"RL: 2.1"--Cover p. [4].
"006-009"--Cover p. [4].
3.1
3-6
3-6
Keywords: Dogs -- Fiction; Pets -- Fiction; Teachers -- Fiction; Responsibility -- Fiction; Dogs -- Fiction; Pets -- Fiction; Teachers -- Fiction; Responsibility -- Fiction